PROSES PEMBERIAN KREDIT USAHA RAKYAT (KUR) PADA BANK RAKYAT INDONESI (BRI) UNIT SUNGAYANG KECAMATAN SUNGAYANG KABUPATEN TANAH DATAR - Naufal Raid; Yurismen Efendi; Yoka Meidian (Jurnal Public Administration, Business and Rural Development Planning, 2021)
The research objectives are: 1) To find out how the process of providing People's Business Credit (KUR) at Bank Rakyat Indonesia (BRI) Sungayang Unit, Sungayang District, Tanah Datar Regency, 2) To find out how the obstacles are faced, 3) To find out how efforts are being made to overcome the obstacles encountered.This study uses a descriptive method. Based on the result of analysis data authors draw the following conclusions: 1) The process of granting People's Business Credit (KUR) at Bank Rakyat Indonesia (BRI) Sungayang Unit, Sungayang District, Tanah Datar Regency consists of: Credit Application Stage, Credit Analysis Stage / Examination Stage , Stage of Giving Credit Decision, Stage of Credit Disbursement/Credit Agreement and Stage of Repayment of Credit Facilities. 2) Obstacles faced include: non-performing loans and the decreasing number of debtors of People's Business Credit (KUR). 3) Efforts are being made to overcome the obstacles faced, including: conducting continuous collections and tightening credit analysis and carrying out socialization of People's Business Credit (KUR) to the public and related parties, that people's business loans are for productive businesses that emphasize feasibility. Keywords: Process, people's business credit